Method for determining crack density in pole piece, method for determining conductive agent content in pole piece and pole piece

Through the combination of scanning electron microscope and related software, the crack density in the lithium-ion battery electrode is accurately measured, which solves the problem of measurement difficulties in the prior art and provides important data to improve the battery cycle life.

CN117554402BActive Publication Date: 2025-03-28BEIJING ELECTRIC VEHICLE
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311308995.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-03-28
Estimated Expiration
2043-10-10

AI Technical Summary

Technical Problem

The prior art is difficult to accurately measure the density of in-plane cracks in lithium-ion battery electrodes, which affects the cycle life and performance of the battery.

Method used

Scanning electron microscope is used to scan the electrode sheet, extract the crack profile, and obtain the crack density by calculating. The specific steps include using Mimics medical software for Gaussian filtering and grayscale threshold segmentation, and finally using HyperMesh software to calculate the crack density.

Benefits of technology

Accurate measurement of crack density in pole sheets is achieved, important data is provided to guide the design of high-capacity and long-life pole sheets, and improve the cycle life of the entire vehicle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117554402B_ABST
    Figure CN117554402B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for determining crack density in a pole piece, a method for determining the content of a conductive agent in a pole piece, and a pole piece. The method for determining crack density in a pole piece comprises performing a scanning electron microscope on the pole piece to obtain a scanning electron microscope image, wherein cracks are present in the scanning electron microscope image; extracting the crack profile of the scanning electron microscope image; and calculating the crack density of the scanning electron microscope image according to the crack profile of the scanning electron microscope image. The method of the present invention can quantitatively measure the crack density in the pole piece.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of batteries, and in particular, relates to a method for determining crack density in a pole piece, a method for determining the content of a conductive agent in a pole piece, and a pole piece. Background Art

[0002] With the development of science and technology, lithium-ion batteries have shown advantages over other energy storage technologies in providing power for new energy vehicles and electronic products such as computers, and have become a popular battery system. In recent years, engineering and scientific issues related to lithium-ion batteries have attracted extensive research in various industries.

[0003] The mechanical damage caused by the fracture of the active layer of the battery pole piece will lead to the decline of electrochemical performance. Among them, the conductive agent is an important component of the active layer. Most researchers have only studied the cracking of the active layer on the surface of the pole piece caused by electrochemical cycling, but have not quantitatively studied the impact of cracks on the performance of lithium-ion batteries before and after the cycle of the pole piece. Therefore, accurate measurement of cracks in the active layer is of great significance for guiding the design of high-capacity and long-life pole pieces. Finding the optimal crack density is particularly important for improving the cycle life of the entire vehicle. Summary of the invention

[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the present application provides a method for determining crack density in a pole piece, which can accurately measure the crack density in the pole piece.

[0005] In the first aspect of the present invention, a method for determining the crack density in a pole piece is proposed. According to an embodiment of the present invention, the method includes performing a scanning electron microscope on the pole piece to obtain a scanning electron microscope image, wherein there are cracks in the scanning electron microscope image; extracting the crack contour of the scanning electron microscope image; and calculating the crack density of the scanning electron microscope image based on the crack contour of the scanning electron microscope image.

[0006] According to the method for determining the crack density in the pole piece of the above embodiment of the present invention, the pole piece is first scanned using a scanning electron microscope to obtain a scanning electron microscope image of the pole piece, through which the cracks on the surface of the pole piece can be directly observed, and then the crack profile in the scanning electron microscope image of the pole piece is extracted, and then the crack density of the crack in the scanning electron microscope image is calculated based on the crack profile. Therefore, the crack density in the pole piece can be accurately measured by using the method for determining the crack density in the pole piece of the present application.

[0007] In addition, the determination method according to the above embodiment of the present invention may have the following additional technical features:

[0008] In some embodiments of the present invention, the step of extracting the crack profile of the scanning electron microscope image includes: extracting the crack profile of the scanning electron microscope image using Mimics medical software. Thus, the crack profile in the scanning electron microscope image can be accurately extracted, which is conducive to accurately calculating the crack density in the pole piece.

[0009] In some embodiments of the present invention, the step of extracting the crack contour of the scanning electron microscope image using Mimics medical software includes using Mimics medical software to perform Gaussian filtering on the scanning electron microscope image to obtain an intermediate image; and setting a grayscale threshold on the intermediate image to obtain the crack contour of the scanning electron microscope image. In this way, a clear crack contour in the scanning electron microscope image can be obtained, which is conducive to accurately calculating the crack density in the pole piece.

[0010] In some embodiments of the present invention, the grayscale threshold α satisfies: 0<α≤23000. Thus, a clear crack outline in the scanning electron microscope image can be extracted, which is beneficial for accurately calculating the crack density in the pole piece.

[0011] In some embodiments of the present invention, the crack density is calculated using Hypermes software, thereby being able to accurately calculate the crack density in the pole piece.

[0012] In the second aspect of the present invention, the present invention proposes a method for determining the content of a conductive agent in a pole piece. The method comprises preparing a plurality of pole pieces with different conductive agent mass contents; using the above method to determine the crack density in the plurality of pole pieces; if the crack density in the pole piece is within 0.025 μm / μm 2 -0.04μm / μm 2 If the conductive agent is within the range, the corresponding conductive agent mass content is determined to be the conductive agent mass content in the electrode. Therefore, it can be shown that the conductive agent has a regulating effect on the crack density of the electrode.

[0013] In some embodiments of the present invention, the pole piece includes a current collector and an active material layer disposed on at least one side of the current collector, and the mass content of the conductive agent is 6.25%-40% based on the total mass of the active material layer. Thus, the crack density in pole pieces with different contents of conductive agent can be accurately measured.

[0014] In some embodiments of the present invention, the conductive agent includes at least one of carbon nanotubes, conductive carbon, acetylene black, carbon black, Ketjen black, carbon dots, Super P (SP), graphene and carbon nanofibers.

[0015] In some embodiments of the present invention, the current collector includes at least one of copper foil and aluminum foil.

[0016] In the third aspect of the present invention, the present invention provides a pole piece, the pole piece includes a current collector and an active material layer disposed on at least one side of the current collector, the active material layer includes a conductive agent, and the mass content of the conductive agent is 21%-28% based on the total mass of the active material layer. Thus, by limiting the mass content of the conductive agent to the above range, a suitable crack density can be obtained in the pole piece, which is conducive to improving the cycle performance of the battery.

[0017] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0019] Figure 1 A schematic diagram of a flow chart of an embodiment of the present invention is shown;

[0020] Figure 2 The scanning electron microscope image of the pole piece of Example 1 of the present invention is shown;

[0021] Figure 3 A picture showing the crack profile of the pole piece of Example 1 of the present invention;

[0022] Figure 4 The graph shows the variation of the crack density in the pole pieces of Examples 1-9 of the present invention with the change of the mass content of carbon nanotubes. DETAILED DESCRIPTION

[0023] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0024] With the development of science and technology, lithium-ion batteries have shown advantages over other energy storage technologies in providing power for new energy vehicles and electronic products such as computers, and have become a popular battery system. In recent years, engineering and scientific issues related to lithium-ion batteries have attracted extensive research in various industries.

[0025] The mechanical damage caused by the fracture of the active layer of the battery pole piece will lead to the degradation of the electrochemical performance. Among them, the conductive agent is an important component of the active layer. Most researchers have only studied the cracking of the active material layer on the surface of the pole piece caused by electrochemical cycling, but have not quantitatively studied the impact of the cracks in the active material layer before the pole piece cycle on the performance of lithium-ion batteries. Therefore, accurate measurement of cracks in the active material layer of the electrode pole piece is of great significance for guiding the design of high-capacity and long-life pole pieces. Finding the optimal crack density is particularly important for improving the cycle life of the entire vehicle.

[0026] In one aspect of the present invention, a method for determining crack density in a pole piece is provided. Figure 1 , the method for determining the crack density in the pole piece includes:

[0027] S100: Perform a scanning electron microscope on the electrode to obtain a scanning electron microscope image, and cracks are found in the scanning electron microscope image.

[0028] In this step, the pole piece is placed in a scanning electron microscope for scanning electron microscopy so that a scanning electron microscope image with cracks can be obtained. It should be noted that a scanning electron microscope (SEM) is an observation method between a transmission electron microscope and an optical microscope. An electron beam is used to scan the surface of a material. When the electron beam hits the surface of the material, electron absorption and emission phenomena will occur. They will reflect particles or be absorbed. These reflected particles will be received by the detector to form a morphological image of the material. Therefore, the cracks in the scanning electron microscope image can be clearly obtained using a scanning electron microscope.

[0029] S200: extracting the crack profile of the scanning electron microscope image.

[0030] In this step, cracks in the pole piece scanning electron microscope image are extracted, which is beneficial to the subsequent calculation of crack density.

[0031] In some embodiments of the present invention, the step of extracting the crack contour of the scanning electron microscope image includes: using Mimics medical software to extract the crack contour of the scanning electron microscope image. It should be noted that Mimics medical software is an interactive image control system of Materialise, which can quickly process images, and the processed images are very clear without being unclear or blurred. Therefore, the above-mentioned software is used to extract cracks in the scanning electron microscope image, and a clear crack contour image can be quickly obtained, which is conducive to the subsequent accurate calculation of the crack density.

[0032] It should be noted that the crack density refers to the length of the crack per unit area.

[0033] In some embodiments of the present invention, the step of extracting the crack contour of the scanning electron microscope image using Mimics medical software includes using Mimics medical software to perform Gaussian filtering on the scanning electron microscope image to obtain an intermediate image. In the scanning electron microscope image, there are not only cracks, but also other substances similar to cracks, such as other substances that may include particles in the active material layer, etc. These similar substances will affect the extraction of the crack contour, and then cause the calculated crack density to be inaccurate. Therefore, this embodiment uses Mimics medical software to perform Gaussian filtering on the scanning electron microscope image, and by setting the variance value of the Gaussian discrete, the image is slightly blurred, and an intermediate image can be obtained, which is conducive to extracting a true and accurate crack density.

[0034] It should be noted that Gaussian filtering is essentially a signal filtering method that can eliminate Gaussian noise. Its purpose is to smooth the signal to obtain an image with a high signal-to-noise ratio, which can reflect the real signal in the image.

[0035] Furthermore, the intermediate image is segmented by grayscale threshold to obtain the crack outline of the scanning electron microscope image. After the scanning electron microscope image is processed by Gaussian filtering, the crack in the intermediate image obtained has different grayscale values ​​from the background in the image, so the crack outline can be extracted according to the difference in grayscale values ​​between the crack and the background. Specifically, in the Mimics medical software, by setting a suitable grayscale threshold, the grayscale of the image is divided into two parts according to the maximum inter-class variance.

[0036] It should be noted that the maximum inter-class variance is a dynamic threshold segmentation algorithm. Its main idea is to divide the image into two parts, background and crack, according to the grayscale characteristics. The basis for division is to select a threshold value so that the variance between the background and the crack is the largest. Among them, the larger the inter-class variance between the background and the crack, the greater the difference between the two parts. When part of the crack is wrongly classified as the background or part of the background is wrongly classified as a crack, the difference between the two parts will become smaller. Therefore, the segmentation using the maximum inter-class variance means the minimum probability of misclassification. Grayscale threshold segmentation is to divide the grayscale of the image into different levels, and then determine the grayscale, the threshold method, which is actually a binarization process, that is, select a threshold to convert the image into a black and white binary image for image segmentation and edge extraction.

[0037] In some embodiments of the present invention, the grayscale threshold α satisfies: 0<α≤23000, for example, it can be 0, 500, 1000, 5000, 10000, 20000, 23000, etc. In the process of image grayscale threshold segmentation, the grayscale threshold should not be selected too large or too small, which will greatly affect the segmentation effect. Therefore, in the process of using grayscale threshold segmentation, the selection of grayscale threshold is very important. Therefore, limiting the grayscale threshold within the above range can obtain a clear crack contour, which is conducive to the quantitative calculation of crack density.

[0038] S300: Calculating the crack density of the scanning electron microscope image according to the crack profile of the scanning electron microscope image, that is, the crack density in the pole piece.

[0039] In this step, the medium crack density can be quantitatively obtained by calculating the crack profile in the scanning electron microscope image of the pole piece.

[0040] In some embodiments of the present invention, the crack density is calculated using HyperMesh software. HyperMesh is a powerful finite element software that can support the import of geometric models and finite element models in various formats. Therefore, the crack density in the pole piece can be accurately calculated using the HyperMesh software.

[0041] In the second aspect of the present invention, the present invention proposes a method for determining the content of a conductive agent in a pole piece. According to an embodiment of the present invention, the method for determining the content of a conductive agent in a pole piece comprises preparing a plurality of pole pieces with different conductive agent mass contents; using the above-mentioned method for determining the crack density in a pole piece to determine the crack density in the plurality of pole pieces; if the crack density in the pole piece is within 0.025 μm / μm 2 -0.04μm / μm 2 In the range, for example, the crack density can be 0.025 μm / μm 2 , 0.028μm / μm 2 , 0.03μm / μm 2 , 0.035μm / μm 2 , 0.04μm / μm 2 Etc., then the corresponding conductive agent mass content is determined as the conductive agent content in the pole piece. By preparing pole pieces with different conductive agent mass contents and quantitatively calculating the crack density in different pole pieces, it is revealed that the conductive agent has a regulating effect on the crack density in the pole piece. Different contents of the conductive agent lead to different crack densities, which can then obtain a battery with the best cycle performance, and thus the optimal crack density can be inferred. Therefore, limiting the crack density in the pole piece to the above range is conducive to obtaining a battery with better cycle performance.

[0042] In addition, the addition of conductive agents can increase the conductivity of the pole pieces, which is beneficial to improving the cycle performance of the battery. Taking carbon nanotubes as an example, carbon nanotubes have a unique network structure that can increase the conductivity of the pole pieces. It is generally believed that the more carbon nanotubes there are, the better the battery performance. In addition, the addition of carbon nanotubes can also cause initial defects in the pole pieces (i.e. cracks in the pole pieces). Appropriate cracks can also enhance the cycle performance of the battery.

[0043] In some embodiments of the present invention, the pole piece includes a current collector and an active material layer disposed on at least one side of the current collector. Based on the total mass of the active material layer, the mass content of the conductive agent is 6.25%-40%. For example, the mass content of the conductive agent can be 6.25%, 10%, 15%, 20%, 25%, 30%, 40%, etc. The conductive agent is an important component of the active material layer in the electrode pole piece. When other components in the active material layer are controlled to be the same, changing the content of the conductive agent will cause the initial crack density in the pole piece to change. Taking carbon nanotubes as a conductive agent as an example, since carbon nanotubes are hydrophobic materials, hydrophobic groups and water molecules repel each other, causing carbon nanotube powder to aggregate into agglomerates. Therefore, the more carbon nanotubes, the greater the crack density. Therefore, limiting the mass content of the conductive agent within the above range is conducive to calculating the crack density in the pole piece.

[0044] It should be noted that there is no particular limitation on the specific types of the conductive agent and the current collector in the present invention, and those skilled in the art can flexibly select according to actual conditions. For example, the conductive agent includes at least one of carbon nanotubes, carbon nanotubes, acetylene black, carbon black, Ketjen black, carbon dots, Super P (SP), graphene and carbon nanofibers. The current collector includes at least one of copper foil and aluminum foil.

[0045] In the third aspect of the present invention, the present invention proposes a pole piece. According to an embodiment of the present invention, the pole piece includes a conductive agent, a current collector and an active material layer disposed on at least one side of the current collector, and the mass content of the conductive agent in the pole piece is determined by the above method. Based on the total mass of the active material layer, the mass content of the conductive agent is 21%-28%. For example, the mass content of the conductive agent can be 21%, 23%, 24%, 26%, 28%, etc. The addition of the conductive agent can increase the conductivity of the pole piece, thereby helping to improve the cycle performance of the battery. Taking carbon nanotubes as an example, carbon nanotubes have a unique network structure that can increase the conductivity of the pole piece. It is generally believed that the more carbon nanotubes there are, the better the performance of the battery. In addition, the addition of carbon nanotubes can also cause initial defects in the pole piece (i.e., cracks appear in the pole piece). Suitable cracks can also enhance the cycle performance of the battery. Therefore, by limiting the mass content of the conductive agent within the above range, a suitable crack density can be obtained, thereby helping to improve the cycle performance of the battery.

[0046] It should be noted that the crack density can be obtained by the method described in the first aspect.

[0047] The scheme of the present disclosure will be explained below in conjunction with the examples. Those skilled in the art will appreciate that the following examples are only used to illustrate the present disclosure and should not be considered to limit the scope of the present disclosure. Where specific techniques or conditions are not indicated in the examples, the techniques or conditions described in the literature in this area or the product instructions are used. Where the manufacturers of reagents or instruments are not indicated, they are all conventional products that can be obtained commercially.

[0048] Example 1

[0049] (1) Sodium alginate is used as a binder and carbon nanotubes (diameter 10 nm, TCI) are used as a conductive agent. The mass ratio of silicon powder (particle size 100 nm, Sigma-Aldrich) to sodium alginate is 2:1, and the mass content of carbon nanotubes (diameter 10 nm, TCI) is 25%. First, deionized water is used as a solvent to dissolve sodium alginate, and a stirrer (ARE-310, THINKY) is used to stir for 30 minutes to obtain a uniform sodium alginate solution; then silicon powder and carbon nanotubes are placed in the sodium alginate solution and stirred to obtain a uniform electrode slurry. Subsequently, the scraper scale is adjusted, and the slurry is evenly coated on a 10 μm thick copper foil using a coating machine; after the electrode coating is completed, the electrode is placed in a drying oven (SIOM) at 70°C for 10 hours, and the electrode sheet is cut into a circular electrode sheet with a diameter of 10 mm using a slicer, and then dried again at 70°C for 5 hours to obtain a silicon mass loading of 0.38 mg / cm 2 Silicon composite electrode;

[0050] (2) The silicon composite electrode was scanned by a scanning electron microscope (SEM) to obtain a scanning electron microscope image of the surface of the silicon composite electrode before cycling, and a large number of cracks were found on the electrode surface;

[0051] (3) Mimics medical software was used to perform Gaussian filtering on the scanning electron microscope image. The image was slightly blurred by setting the variance value of Gaussian discreteness to obtain the intermediate image. The grayscale threshold was then set to 10,000, and the intermediate image was segmented by grayscale threshold to extract the crack contour.

[0052] (4) The crack density is calculated using the finite element analysis pre-processing software HyperMesh.

[0053] (5) Preparation of button cells: The circular electrode sheet prepared above is used as the negative electrode, the circular small lithium sheet is used as the counter electrode, a glass fiber diaphragm is used as the isolation membrane, and an electrolyte (1M LiPF6 dissolved in 1:1 vol% EC:DEC) is injected to assemble a button cell.

[0054] The determination of the crack density in the pole piece of Example 2-11 is the same as that of Example 1 except for different experimental parameters (see Table 1).

[0055] The experimental parameters for determining the crack density in the pole pieces of Examples 1-11 of the present application are shown in Table 1.

[0056] Table 1 Experimental parameters of Examples 1-11 and Comparative Example 1

[0057]

[0058]

[0059] Testing and analysis

[0060] Under the same conditions, the pole pieces prepared in the above examples 1-11 were characterized by scanning electron microscopy (SEM). Figure 2 It can be seen from the SEM image of the electrode obtained in Example 1 that after the electrode slurry is prepared, a large number of cracks are generated on the surface of the electrode after the electrode is coated by a coating machine and dried in a vacuum drying oven. In addition, under the same conditions, the cycle performance of the button batteries prepared in Examples 1-9 above was tested, and the specific test method is as follows:

[0061] Cycle performance: At 25°C, charge the button cell at 0.1C constant current to 1000mV, then discharge at 0.1C constant current to 10mV, and obtain the discharge capacity C0 of the button cell. Then, charge and discharge at 0.1C constant current for 100 cycles, and take the discharge capacity C1 of the 100th cycle. The capacity retention rate of the battery after 100 cycles = C1 / C0×100%.

[0062] The test results are shown in Table 2.

[0063] 2 Test results of Examples 1-11

[0064] Battery capacity retention rate after 100 cycles / % Example 1 55 Example 2 45 Example 3 48 Example 4 50 Example 5 49 Example 6 49 Example 7 49 Example 8 48 Example 9 47 Example 10 55 Embodiment 11 55

[0065] Figure 3 The picture showing the crack profile in the pole piece of Example 1 is shown in FIG. Figure 3 It can be seen that a clear crack outline can be obtained by using Mimics medical software; Figure 4 The graph of the crack density in the pole piece of Examples 1-9 as the mass content of carbon nanotubes changes. From the graph, it can be seen that as the carbon nanotube content increases, the crack density in the silicon composite electrode pole piece shows a monotonically increasing trend, that is, the more carbon nanotubes are added, the greater the crack density, that is, the more cracks there are. When the mass content of carbon nanotubes is 25%, the crack density on the surface of the active layer in the pole piece is 0.035μm / μm2 .

[0066] Combined with Table 2, it can be obtained that when the crack density is 0.035μm / μm 2 When the battery life decays slowly, the battery cycle performance is better. Therefore, the method of the present invention can quantitatively calculate the crack density in the electrode plate. In addition, by preparing plates with different conductive agent mass contents and calculating the crack density in the plates, it can be obtained that the conductive agent has a regulating effect on the crack density in the plates, and the appropriate conductive agent mass content can also be determined, which is beneficial to saving the cost of the conductive agent. In addition, based on the method of the present invention, it is also possible to obtain a suitable crack density, which is beneficial to improving the cycle performance of the battery, which is of great significance to the improvement of the cycle performance of the whole vehicle.

[0067] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", "some implementation schemes" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0068] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for determining the content of a conductive agent in a pole piece, characterized in that: include: preparing a plurality of pole pieces with different conductive agent mass contents; The plurality of pole pieces differ only in the mass content of the conductive agent; Performing scanning electron microscopy on the electrode to obtain a scanning electron microscopy image, wherein cracks are present in the scanning electron microscopy image; extracting a crack profile from the scanning electron microscope image; According to the crack profile of the scanning electron microscope image, the crack density of the scanning electron microscope image is calculated, that is, the crack density in the pole piece; The step of extracting the crack profile of the scanning electron microscope image comprises: extracting the crack profile of the scanning electron microscope image using Mimics medical software; The steps of extracting the crack profile of the scanning electron microscope image using Mimics medical software include: Mimics medical software was used to perform Gaussian filtering on the scanning electron microscope image to obtain an intermediate image; Performing grayscale threshold segmentation on the intermediate image to obtain the crack contour of the scanning electron microscope image, and determining the crack density of the plurality of pole pieces; If the crack density of the pole piece is 0.025 μm / μm 2 -0.04μm / μm 2 If the crack density of the electrode is within the range of 21% to 28%, the corresponding mass content of the conductive agent is determined, and the mass content of the conductive agent in the electrode corresponding to the crack density of the above-mentioned electrode is obtained.

2. The method according to claim 1, characterized in that The grayscale threshold α satisfies: 0<α≤23000.

3. The method according to any one of claims 1 to 2, characterized in that: The crack density is calculated using HyperMesh software.

4. The method for determining the content of conductive agent in a pole piece according to claim 1, characterized in that: The pole piece includes a current collector and an active material layer disposed on at least one side of the current collector, and the active material layer includes a conductive agent.

5. The method according to claim 4, characterized in that The conductive agent includes at least one of carbon nanotubes, conductive carbon, acetylene black, carbon black, Ketjen black, carbon dots, Super P (SP), graphene and carbon nanofibers.

6. The method according to claim 5, characterized in that The current collector includes at least one of copper foil and aluminum foil.

Citation Information

Patent Citations

  • Chromium-ceramic composite coating reticulate crack quantitative detection method

    CN107316290A

  • Lithium battery negative plate, preparation method thereof and lithium battery

    CN112086622A

  • Negative electrode sheet, secondary battery comprising same, and electric device

    CN116682974A